2002
DOI: 10.1002/art.10367
|View full text |Cite
|
Sign up to set email alerts
|

Use of joint fluid analysis for determining cartilage damage in osteonecrosis of the knee

Abstract: Objective. To assess the value of joint fluid analysis for determining cartilage degradation and prognosis in spontaneous osteonecrosis (ON) of the knee. Results. The mean ؎ SD level of C6S was 82.2 ؎ 36.6 nmoles/ml in joint fluid from ON knees, which was significantly higher than the levels in knees with grade 2 (47.2 ؎ 20.0 nmoles/ml) and grade 3 (55.8 ؎ 29.2 nmoles/ml) OA. The C6S:C4S ratio was highest in lesions with mild articular changes and reflected the macroscopic alteration of cartilage overlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…For example, although the average molecular weight of hyaluronan in synovial fluid from normal joints varied from 2.75 to 10.9 MDa, compared with 1.8 to 2.1 MDa in synovial fluid from patients with OA [8,[22][23][24][25] , each study reported results from patients with or without OA, but the 2 groups were not directly compared in the same study. Similarly, although the average concentration of hyaluronan in synovial fluid (weighted by number of patients) was 1.7 mg/ml in patients with OA [8,23,[26][27][28][29][30][31][32] , and 2.5 mg/ml in the controls, the variance in the data was too great to permit accepting the difference as statistically valid. Still worse, almost none of the studies considered the possible confounding effects of the age of the subject.…”
Section: Discussionmentioning
confidence: 98%
“…For example, although the average molecular weight of hyaluronan in synovial fluid from normal joints varied from 2.75 to 10.9 MDa, compared with 1.8 to 2.1 MDa in synovial fluid from patients with OA [8,[22][23][24][25] , each study reported results from patients with or without OA, but the 2 groups were not directly compared in the same study. Similarly, although the average concentration of hyaluronan in synovial fluid (weighted by number of patients) was 1.7 mg/ml in patients with OA [8,23,[26][27][28][29][30][31][32] , and 2.5 mg/ml in the controls, the variance in the data was too great to permit accepting the difference as statistically valid. Still worse, almost none of the studies considered the possible confounding effects of the age of the subject.…”
Section: Discussionmentioning
confidence: 98%
“…Since CS stabilizes fibrous and cellular elements of the connective tissue and at the same time lubricates and protects the membranes in joints, [4][5][6][7] CS has become increasingly popular as an ingredient in health foods for the symptomatic treatment of osteoarthritis. However, CS is poorly absorbed through the gastrointestinal tract because of its high molecular weight (MW) (5-50 kDa) and highly negative surface charge.…”
Section: 3)mentioning
confidence: 99%
“…CS in particular stabilizes fibrous and cellular elements of the connective tissue and at the same time lubricates and protects the membranes in joints. [4][5][6][7] Because of this, CS has become increasingly popular as an ingredient in "health foods", and has been unlawfully advertised as effective in the treatment of symptoms related to arthritis and cartilage repair, though several proprietary drugs approved in Japan contain CS as an effective constituent.…”
mentioning
confidence: 99%